2016
DOI: 10.1038/nature20598
|View full text |Cite
|
Sign up to set email alerts
|

A 17-gene stemness score for rapid determination of risk in acute leukaemia

Abstract: Refractoriness to induction chemotherapy and relapse after achievement of remission are the main obstacles to cure in acute myeloid leukaemia (AML). After standard induction chemotherapy, patients are assigned to different post-remission strategies on the basis of cytogenetic and molecular abnormalities that broadly define adverse, intermediate and favourable risk categories. However, some patients do not respond to induction therapy and another subset will eventually relapse despite the lack of adverse risk f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

42
943
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 717 publications
(1,045 citation statements)
references
References 50 publications
42
943
2
2
Order By: Relevance
“…Furthermore, gene set enrichment analysis 29,30 revealed that genes upregulated in human leukemia stem cells (LSCs) were more enriched in the leukemic bone marrow cells compared with the cultured cells, whereas genes downregulated in human LSCs were enriched in the cultured cells used for injection ( Figure 7B). 31 These data suggested that LSCs may be more abundant in AML in vivo than in cultured genomeedited cells, consistent with much shorter latencies for disease emergence in secondary transplanted mice ( Figure 6B). Thus, although t(9;11) may be sufficient for development of AML from genome-edited primary human cells, environmental or nongenetic factors may also influence disease progression.…”
Section: Org Fromsupporting
confidence: 62%
“…Furthermore, gene set enrichment analysis 29,30 revealed that genes upregulated in human leukemia stem cells (LSCs) were more enriched in the leukemic bone marrow cells compared with the cultured cells, whereas genes downregulated in human LSCs were enriched in the cultured cells used for injection ( Figure 7B). 31 These data suggested that LSCs may be more abundant in AML in vivo than in cultured genomeedited cells, consistent with much shorter latencies for disease emergence in secondary transplanted mice ( Figure 6B). Thus, although t(9;11) may be sufficient for development of AML from genome-edited primary human cells, environmental or nongenetic factors may also influence disease progression.…”
Section: Org Fromsupporting
confidence: 62%
“…In a recent study of Ng et al, the four CD34/CD38 defined cell populations of AML patients were sorted and were subsequently injected into mice and screened for their leukemia-initiating ability [13]. This exquisite approach confirmed that LSC activity was detected in all fractions; however, with a majority of CD34+ fractions, especially CD34+/CD38−, and minority of CD34− fractions containing LSC.…”
Section: Identification Of Leukemic Stem Cellsmentioning
confidence: 70%
“…However, the SHB/PAX5/HDAC/BCORL1/TET1 network shows only limited resemblance to the poor prognosis of 17-gene stemness signature. 33 Currently, when addressing the functional significance of the overlap in co-expression between SHB/PAX5/HDAC7/ BCORL1/TET1 by ToppGene analysis, certain phenotypic characteristics can be observed. The most extensive list of biological functions appeared among SHB/PAX5 coexpressed genes in which functions relating to immune cell activation dominated.…”
Section: Discussionmentioning
confidence: 99%